Identification and characterization of genes related to salt stress tolerance within segregation distortion regions of genetic map in F2 population of upland cotton. - Muhammad Shehzad; Zhongli Zhou; Allah Ditta; Majid Khan; Xiaoyan Cai; Yanchao Xu; Amir Maqbool; Ahlam Khalofah; Muhammad Shaban; Muhammad Naeem; Mohammad Javed Ansari; Kunbo Wang; et al. (PLoS ONE)
Segregation distortion (SD) is a genetic mechanism commonly found in segregating or stable populations. The principle behind this puzzles many researchers. The F2 generation developed from wild Gossypium darwinii and G. hirsutum CCRI12 species was used to investigate the possible transcription factors within the segregation distortion regions (SDRs). The 384 out of 2763 markers were distorted in 29 SDRs on 18 chromosomes. Good collinearity was observed among genetic and physical maps of G. hirsutum and G. barbadense syntenic blocks. Total 568 genes were identified from SDRs of 18 chromosomes. Out of these genes, 128 belonged to three top-ranked salt-tolerant gene families. The DUF597 contained 8 uncharacterized genes linked to Pkinase (PF00069) gene family in the phylogenetic tree, while 15 uncharacterized genes clustered with the zinc finger gene family. Two hundred thirty four miRNAs targeted numerous genes, including ghr-miR156, ghr-miR399 and ghr-miR482, while others targeted top-ranked stress-responsive transcription factors. Moreover, these genes were involved in the regulation of numerous stress-responsive cis-regulatory elements. The RNA sequence data of fifteen upregulated genes were verified through the RT-qPCR. The expression profiles of two highly upregulated genes (Gh_D01G2015 and Gh_A01G1773) in salt-tolerant G. darwinii showed antagonistic expression in G. hirsutum. The results indicated that salt-tolerant genes have been possibly transferred from the wild G. darwinii species. A detailed functional analysis of these genes can be carried out which might be helpful in the future for gene cloning, transformation, gene editing and the development of salt-resistant cotton varieties.